A scoping review of implementation of health-focused interventions in vulnerable populations. Issue 9 (7th October 2022) - Daniels, Sarah I; Cheng, Hannah; Gray, Caroline; Kim, Bo; Stave, Christopher Donald; Midboe, Amanda M
Abstract: Vulnerable populations face significant challenges in getting the healthcare they need. A growing body of implementation science literature has examined factors, including facilitators and barriers, relevant to accessing healthcare in these populations. The purpose of this scoping review was to identify themes relevant for improving implementation of healthcare practices and programs for vulnerable populations. This scoping review relied on the methodological framework set forth by Arksey and O'Malley, and the Consolidated Framework for Implementation Research (CFIR) to evaluate and structure our findings. A framework analytic approach was used to code studies. Of the five CFIR Domains, the Inner Setting and Outer Setting were the most frequently examined in the 81 studies included. Themes that were pertinent to each domain are as follows— Inner Setting : organizational culture, leadership engagement, and integration of the intervention; Outer Setting : networks, external policies, and patients' needs and resources ; Characteristics of the Individual : knowledge and beliefs about the intervention, self-efficacy, as well as stigma (i.e., other attributes ); Intervention Characteristics : complexities with staffing, cost, and adaptations ; and Process : staff and patient engagement, planning, and ongoing reflection and evaluation . Key themes, including barriers and facilitators, are highlighted here as relevant to implementation of practices for vulnerable populations. These findings can inform tailoring of implementation strategies and health policies for vulnerable populations, thereby supporting more equitable healthcare. Lay Summary: People with certain physical or mental health conditions and/or socioeconomic challenges can experience poor health outcomes (herein referred to as vulnerable populations). A growing body of research has focused on the evaluation of implementation of practices and programs among vulnerable populations; however, little work has summarized the factors that impact successful implementation. This scoping review takes advantage of a structured framework, the Consolidated Framework for Implementation Research, to organize relevant implementation factors from implementation studies among vulnerable populations into one of five categories: inner setting, outer setting, intervention characteristics, characteristics of the individual, and process. Overall, findings showed that engagement in the intervention must occur at all levels of the organization with careful planning and evaluation. Successful implementation requires facilitating a supportive culture, belief in the intervention, and self-efficacy from the providers and patients. Stigma, patient needs, and practical issues of staffing and cost for the intervention are common barriers to be addressed. Findings from this review provide guidance for future implementation efforts among vulnerable populations and inform health policies to support more equitable health care. Abstract : This review identifies facilitators and barriers that can inform implementation efforts focused on improving the health of individuals from vulnerable populations.